2009
DOI: 10.1186/1471-2105-10-185
|View full text |Cite
|
Sign up to set email alerts
|

Automated genome mining for natural products

Abstract: Background: Discovery of new medicinal agents from natural sources has largely been an adventitious process based on screening of plant and microbial extracts combined with bioassayguided identification and natural product structure elucidation. Increasingly rapid and more costeffective genome sequencing technologies coupled with advanced computational power have converged to transform this trend toward a more rational and predictive pursuit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
163
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(170 citation statements)
references
References 37 publications
1
163
0
1
Order By: Relevance
“…In the future, specific algorithms can be developed that will overcome this limitation, especially in conjunction with high-resolution MS/MS data. Instead of carrying out peptidogenomics analysis on a single organism as previously described, the peptide backbones of all of the NRPS gene clusters from all available genome sequences of bacilli and pseudomonads in the public databases were predicted using a batch form of antibiotics and Secondary Metabolite Analysis SHell (antiSMASH) as well as curation using other Adomain prediction tools (4,16,43,44,57) (Tables S2 and S3). By combining amino acid MS/MS signatures with the predicted amino acid specificity of NRPS A domains, we obtained candidate matches of MS/MS signatures to particular GCFs.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…In the future, specific algorithms can be developed that will overcome this limitation, especially in conjunction with high-resolution MS/MS data. Instead of carrying out peptidogenomics analysis on a single organism as previously described, the peptide backbones of all of the NRPS gene clusters from all available genome sequences of bacilli and pseudomonads in the public databases were predicted using a batch form of antibiotics and Secondary Metabolite Analysis SHell (antiSMASH) as well as curation using other Adomain prediction tools (4,16,43,44,57) (Tables S2 and S3). By combining amino acid MS/MS signatures with the predicted amino acid specificity of NRPS A domains, we obtained candidate matches of MS/MS signatures to particular GCFs.…”
Section: Significancementioning
confidence: 99%
“…This wealth of sequence data has the potential to be used for the discovery of small bioactive molecules through genome mining (1)(2)(3)(4)(5)(6). Genome mining is a process in which small molecules are discovered by predicting what compound will be genetically encoded based on the sequences of biosynthetic gene clusters.…”
mentioning
confidence: 99%
“…Oftentimes, the distribution of the ion of interest is interfacial and the producer is ambiguous. By employing analytical and biological approaches, such as microbial IMS, IMS of multiple time points (67), traditional solvent extraction, purification, and structural determination methods, such as tandem MS and nuclear magnetic resonance (NMR) (18,30,33,67,68), genetics and microbiology, 16S rRNA sequencing (54), established MALDI-TOF protocols (12,49,53), genome mining approaches (7,13,15,45,63) and predictive programs (2,3,16,33, 40,48,55,62,65,68), peptidogenomics (31), and literature and database searches (23, 52) (AntiMarin database, Dictionary of Natural Products, the National Institute of Standards and Technology [NIST] databases, and the SciFinder database), one can typically annotate microbial IMS data. Two main strategies to confirm the producing microbe and the resultant phenotype are genetic knockout and complementation studies or assays with purified compound, in combination with more IMS.…”
Section: Challenges In Microbial Imsmentioning
confidence: 99%
“…Streptomyces is a representative of a filamentous bacteria responsible for producing variety of valuable secondary metabolites, such as antibiotics, parasiticides, herbicides, and pharmacologically active substances, including antitumor agents and immunosuppressants (Waksman and Woodruff, 1940;Ditsler et al, 1992;Euverink, 1995;Newman et al, 2000;El Hassan et al, 2001;Bentley et al, 2002;Bibb, 2005;Quintana et al, 2008;Li et al, 2009;Doroghazi et al, 2014). Genome sequencing analyses of Streptomyces avermitilis (Omura et al, 2001), Streptomyces coelicolor A3(2) (Bentley et al, 2002), Streptomyces griseus IFO 13350 (Ohnishi et al, 2008), and Streptomyces bingchenggensis (Wang et al, 2010) revealed that Streptomyces possess an unexpected abundance of natural product biosynthetic gene clusters and thus that they have the potential to make many more compounds than previously thought.…”
Section: Introductionmentioning
confidence: 99%